Description and characterization of pneumococcal community acquired pneumonia (CAP) among radiologically confirmed CAP in outpatients - Josselin Le Bel; Juliette Pinot; Toni Alfaiate; Marie Ecollan; Fanny Cussac; Raphaël Pecqueur; Marie-Pierre Revel; Cyrille Vartanian; Emmanuelle Varon; Christian Theilacker; Xavier Duval; Henri Partouche; et al. (npj Primary Care Respiratory Medicine)
Abstract Streptococcus pneumoniae (SP) remains an important cause of community acquired pneumonia (CAP). We aimed to describe the prevalence and characteristics of outpatients with radiologically confirmed pneumococcal CAP. Between November 2017 and December 2019, a French network of general practitioners enrolled CAP-suspected adults, with ≥1 clinical signs of infection and ≥1 signs of pulmonary localization in an observational study. Pneumococcal CAP was defined by the combination of a chest X-ray (CXR) compatible with CAP and SP detection by any of four microbiological tests (blood culture, sputum culture, pneumococcal urinary antigen test [BinaxNow®] and serotype-specific multiplex urinary antigen detection test [Pfizer Inc®]. To identify other pathogens, next to cultures, nasopharyngeal multiplex PCR was performed. Three hundred and forty-eight patients were included, of whom 144 had a positive CXR, 135/144 (93.8%) had not received antibiotics prior to inclusion, 21/144 (14.6%) had ≥1 positive microbiological test for SP, and 66/144 (45.8%) were negative for all four microbiological tests and were considered as non-pneumococcal CAP. Pneumococcal serotypes were identified for 12 patients. This study assessing the prevalence of SP among CAP outpatients using comprehensive microbiologic testing shows that SP is still the most frequently identified microorganism.